Dominant Factors Affecting HIV AIDS Prevention In The Village “X” Bongas District Of Indramayu In 2023 - Wardani, Siti Pangarsi Dyah Kusuma; Astuti, Nur Mega; Nuraeni, Tating (Gema Wiralodra, 2024)
Data from the health service of Indramayu district in 2021 showed that the number of cases of HIV AIDS was 4,849 per incidence in Indramayu district, with the highest cases in Bongas district being 392. The research was conducted in the village "X" in Bongas district. This study aims to identify the factors that most influence HIV AIDS prevention attitudes. The subject of the research was the entire village community "X", consisting of 5,553 people with a sample of 100 people, and using a cross-sectional research design and continued with multivariate modeling. Data collection method using a questionnaire. Multivariate data analysis with double logistic regression, univariate with chi square and fisher exact tests, and bivariate tests. Based on the results obtained from respondents with an environmental culture of good HIV/AIDS prevention attitude 38 (32.2), p-value (0.018), respondents who have good social communications related to AIDS HIV prevention stance 60 (58.9) with p-valu (0.279), respondents whose friendship related to HIV AIDS prevention posture is good 49 (42.2) with a p- value (0,003), respondents having knowledge related to a good AIDS HIV-prevention stance 56 (48.4) with a P-valure (0,000), respondants who are exposed to media information about HIV/aids preventive stance 50 (49.0) with the p- value (0.606), respondents have experience with a good HIV-AIDS preventative attitude 50 (44.0) with p -value ( 0,007). There is an influence of environmental culture, friendships, knowledge, and experience on the attitude of HIV AIDS prevention, there is no influence on social communications on the approach of AIDS HIV prevention. Environmental cultural factors are the most dominant factors. Other research is expected to further refine the social capital approach to HIV/AIDS.